PEMANFAATAN BAHAN ORGANIK UNTUK MENINGKATKAN KESADARAN AKAN PENGELOLAAN LIMBAH MELALUI ECO ENZYME - Arman Arman; Bima Arya Renaldie; Dita Riska Nurputri; Elda Mustapidah Yudiantini; Ariena Rosydiena Azkiyatuz Shahifa; Arif Rahman; Ai Sulistiawati; Ai Rosi Nur Aladawiah; Doni Doni; Amelia Nurealita; Dedi Nurjamil; Deviani Deviani; I Wayan Sumandya (LPPM Universitas Bina Bangsa, 2024)
With the increasing human population, waste production, including household waste, has also increased, creating significant management problems. Organic waste, such as vegetable and fruit scraps, decomposes easily and can pollute the environment and produce harmful methane gas. One solution to reduce the negative impact of household organic waste is by making Eco Enzyme, a fermentation product of organic kitchen waste that provides various environmental and health benefits. Therefore, this community service activity aims to raise awareness and skills in waste management through the creation of Eco Enzyme. The implementation method involves a Socialization on Utilizing Waste through Eco Enzyme, held in Dusun Cikatomas, Handapherang Village, Cijeungjing District, Ciamis Regency on Thursday, May 9, 2024. This activity was attended by several PKK members. The steps include four stages: pre-proposal, proposal, main activity, and evaluation. During the service activity, the materials presented were what Eco Enzyme is, how to make it, its benefits, and how to use it. The harvested and packaged Eco Enzyme was distributed to participants for them to experience its benefits firsthand. From the entire socialization series, it was evident that all participants were motivated to try making Eco Enzyme